Variation minimization in tele-sandblasting system: the effect of human-arm movement error - Ranon Jientrakul; Pornsak Attavanish; Pholchai Chotiprayanakul; Sunpasit Limnararat; Chumpol Yuangyai (My University, 2018)
In tele-sandblasting task, human arm movement is a critical source of producing variation in position of sandblasting nozzle resulting in high operating cost and low productivity. Each operator behaves differently leading to unpredictable movements. Skilled operators are able to reduce the variation; however, developing skills requires a training period. In this paper, we proposed a new approach which is the use of a novel operator's arm movement pattern incorporated with a Kalman filter to reduce the effect of human-arm movement error. A virtual tele-sandblasting system is used to validate our approach. The experimental results verify that our proposed approach is able to significantly reduce the effect of human arm movement error. The approach helps operators to perform the task more comfortably and takes short training time.
Keywords: Variation (astronomy); Minification; Teleoperation and Haptic Systems